Potential of entomopathogenic fungi to control insect pests and disease at lettuce and arugula crops - Bellesini Vigna, Fernando; Rensis, Ana Paula Alves Silveira de; Rodrigues, Luís Rodolfo; Oliva, Matheus Barros; Rossi, Marta Maria; Pinto, Alexandre de Sene (Comunicata Scientiae, 2024)
The lettuce (Lactuca sativa L.) (Asteraceae) and arugula (Eruca sativa Miller) (Brassicaceae) crops are attacked by various pests and diseases, but the control is usually done with agrochemicals. We evaluate the control of pests and diseases by systematic applications of the entomopathogenic fungi strains Metarhizium anisopliae IBCB425 and Beauveria bassiana IBCB66 both 300g c.p. in the planting groove and 200 g c.p. ha-1 on the foliage, in weekly applications at lettuce and arugula crops planted in association. For the evaluation of pests and diseases, 15 plants were evaluated at random in three beds per treatment. In the lettuce crop occurred the presence of aphids (Myzus persicae Hemiptera:Aphididae), whiteflies (Bemisia tabaci Hemiptera: Aleyrodidae), thrips (Frankliniella schultzei Thysanoptera:Thripidae), leafhoppers Agallia albidula (Hemiptera: Cicadellidae) and septoria disease (Septoria lactucae). In the arugula crop the same pests occurred, but with any disease. The fungi B. bassiana and M. anisopliae controlled F. schultzei and S. lactucae at lettuce crop, B. tabaci in both crops, but did not control M. persicae and A. albidula in both crops. The fungus B. bassiana decreased the mean number of leaves per plant and the mean of dry mass weight of arugula plants in relation to the control treatment, but the sample size may have interfered with these results. The two fungi could be used as biological control agents of pests and diseases at lettuce and arugula crops, especially in organic farming.